Faculty Senate Minutes, March 27, 2014 - Faculty Senate, Valdosta State University (Valdosta State University Archives and Special Collections, 2014)
Valdosta State University Faculty Senate. "Faculty Senate Minutes, March 27, 2014." (Valdosta State University, 2014).
Keywords: Faculty Senate; Corporate minutes; Valdosta State University